2023
DOI: 10.1186/s41235-023-00488-9
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-choice quizzes improve memory for misinformation debunks, but do not reduce belief in misinformation

Abstract: Fact-checkers want people to both read and remember their misinformation debunks. Retrieval practice is one way to increase memory, thus multiple-choice quizzes may be a useful tool for fact-checkers. We tested whether exposure to quizzes improved people’s accuracy ratings for fact-checked claims and their memory for specific information within a fact check. Across three experiments, 1551 US-based online participants viewed fact checks (either health- or politics-related) with or without a quiz. Overall, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…We also examined fake news reminder effects on belief change. Conditions that improve memory sometimes improve belief accuracy (Wahlheim et al, 2020 ), but this is not always observed (Collier et al, 2023 ; Kemp et al, 2022a ). Here, we compared perceived accuracy of recalled details in phase 3 with baseline ratings from phase 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also examined fake news reminder effects on belief change. Conditions that improve memory sometimes improve belief accuracy (Wahlheim et al, 2020 ), but this is not always observed (Collier et al, 2023 ; Kemp et al, 2022a ). Here, we compared perceived accuracy of recalled details in phase 3 with baseline ratings from phase 1.…”
Section: Methodsmentioning
confidence: 99%
“…We also examined associations between memory and beliefs in retrieved headline details. Although extensive work has examined the effects of misinformation exposure and corrections on belief updating (for a review, see Ecker et al, 2022 ), only a few studies have examined the role of memory in belief updating (Collier et al, 2023 ; Kemp, et al, 2022a ; Swire-Thompson et al, 2023 ; Wahlheim et al, 2020 ). Typical belief updating paradigms collect belief ratings for misinformation statements, correct the misinformation, and then collect belief ratings again for the earlier statements (e.g., Swire et al, 2017 ; Swire-Thompson et al, 2023 ).…”
Section: Perceived Accuracy Of Real and Fake Newsmentioning
confidence: 99%
“…Another alternative is to ask people open-ended questions about their beliefs. That is, instead of asking participants to rate the accuracy of the false claim “China produces 90% of the world’s carbon emissions pollution,” participants instead answer the open-ended question “What do you believe about China producing 90% of the world’s carbon emissions pollution?” (Collier et al, 2023). Such open-ended questions can allow for a broader range of responses and a better understanding of participants’ beliefs (especially when participants have conflicting beliefs).…”
Section: Moving Beyond Simple Measures Of Beliefmentioning
confidence: 99%
“…And indeed, Bird et al (2015) found that people who actively rehearsed the contents of a video were substantially better at recall 8 and 18 days after viewing compared to a group that did no rehearsal. 3 Even in the context of debunking approaches to misinformation, retrieval practice has been shown to improve memory of corrective information, although this improved memory does not necessarily translate to more accurate beliefs (Collier et al, 2023;Fazio et al, 2023).…”
Section: Introductionmentioning
confidence: 99%